Effects of Corporate Governance on Financial Performance of Commercial Banks in Nigeria - Gwaison, Panan Danladi; Maimako, Livinus Nkuri (International Journal of Finance Research, 2021)
In most developing countries, several cases of collapses or failure in the banking sector were witnessed. Nigeria had witnessed several cases and collapsed in the banking sector. This study investigated the effects of corporate governance on the financial performance of commercial banks in Nigeria. The study used the survey research design. A secondary source of data was used for this research. The data were collected from financial statements of the five (5) commercial banks selected from the Nigerian Stock Exchange listing for fourteen financial years (2003 – 2017). The study utilized the panel Least Squares Regression Analysis as the method. The result indicated that board size had significant effects on financial performance (ROA) of commercial banks in Nigeria, board composition had significant effects on financial performance (ROA) of commercial banks in Nigeria, board gender diversity had significant effects on financial performance (ROA) of commercial banks in Nigeria, the audit committee has no significant effects on financial performance (ROA) of commercial banks in Nigeria, and board independence had significant effects on financial performance (ROA) of commercial banks in Nigeria. The study, therefore, concludes that the weak corporate governance structure in Nigeria contributed immensely to the recent crisis experienced in the Nigerian banking sector. The study recommended that banks develop and implement strategic training for board members and senior bank managers. Nigerian banks should appropriately adopt the international codes of corporate governance to meet the need of the Nigerian environment, among other recommendations.